Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1093/mnras/sty2321
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent H2 in DLA at zabs = 2.05: physical conditions through observations and numerical models★

Abstract: We perform detailed spectroscopic analysis and numerical modelling of an H 2 -bearing damped Lyman-α absorber (DLA) at z abs = 2.05 towards the quasar FBQS J2340-0053. Metal absorption features arise from fourteen components spread over ∆v 90 = 114 km s −1 , seven of which harbour H 2 . Column densities of atomic and molecular species are derived through Voigt profile analysis of their absorption lines. We measure total N (H i), N (H 2 ) and N (HD) to be 20.35±0.05, 17.99±0.05 and 14.28±0.08 (log cm −2 ) respe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 100 publications
2
18
3
Order By: Relevance
“…The chosen radiation field has three components: a meta-galactic radiation at appropriate redshift (Haardt & Madau 2012), a synchrotron radiation (power-law continuum) arising from GRB afterglow and a blackbody radiation from in situ star formation. Our GRB-DLA models are similar to our previous QSO-DLA models (Srianand et al 2005a;Shaw et al 2016;Rawlins et al 2018) except that here we have an additional synchrotron radiation arising from GRB afterglows. While the gas is exposed to UV radiation from everywhere it is exposed to GRB afterglow only from one side.…”
Section: Modellingsupporting
confidence: 83%
“…The chosen radiation field has three components: a meta-galactic radiation at appropriate redshift (Haardt & Madau 2012), a synchrotron radiation (power-law continuum) arising from GRB afterglow and a blackbody radiation from in situ star formation. Our GRB-DLA models are similar to our previous QSO-DLA models (Srianand et al 2005a;Shaw et al 2016;Rawlins et al 2018) except that here we have an additional synchrotron radiation arising from GRB afterglows. While the gas is exposed to UV radiation from everywhere it is exposed to GRB afterglow only from one side.…”
Section: Modellingsupporting
confidence: 83%
“…The dust-to-gas ratio in this system could be higher than that observed in the SMC, i.e. κ could be greater than unity, as is possible in high-z absorbers due to different grain chemistry or size (see Shaw et al 2016;Noterdaeme et al 2017;Dutta et al 2017b;Rawlins et al 2018). This is similar to what is inferred from the lack of H i 21-cm absorption towards the red quasar J0956+4046 (see Section 2.1.1 and Gupta et al 2012).…”
Section: H I 21-cm Absorption Towards J1521+5508supporting
confidence: 74%
“…The UVES data include the system at z = 3.09 towards J 1311+2225, recently reported by Noterdaeme et al (2018), where C i together with H2 and CO molecules were detected, the well-known three ESDLA systems at z = 2.402 towards HE0027−1836 (Noterdaeme et al 2007) (for which further data was obtained by Rahmani et al (2013), leading to an improved quality spectrum), at z = 3.85 towards J 0816+1446 (Guimarães et al 2012), at z = 2.48 towards J 2140−0321 Noterdaeme et al (2010), and the DLA system towards J 2340-0053 where HD was reported independently and almost simultaneously by Kosenko & Balashev (2018) and Rawlins et al (2018). For this latter system, we refitted HD together with H2 and C i lines to obtain self-consistent priors on physical parameters that are used to derive the CRIR.…”
Section: Datamentioning
confidence: 80%
“…If the H2 column density is large enough, the less abundant isotopologue, HD, can also be detected (Varshalovich et al 2001). To date, HD lines have been detected only in twelve intervening systems among ∼ 40 confirmed H2-bearing DLAs at high redshift (> 0) (Noterdaeme et al 2008;Balashev et al 2010;Tumlinson et al 2010;Ivanchik et al 2010;Noterdaeme et al 2010;Klimenko et al 2015;Ivanchik et al 2015;Klimenko et al 2016;Noterdaeme et al 2017;Balashev et al 2017;Rawlins et al 2018;Kosenko & Balashev 2018). This number remains limited since the detailed analysis of H2 and HD lines can be done only in high-resolution quasar spectra, which require observations with the largest optical telescopes.…”
mentioning
confidence: 99%